Induction of Salt Tolerance in Arabidopsis thaliana by Volatiles From Bacillus amyloliquefaciens FZB42 via the Jasmonic Acid Signaling Pathway - Liu, Shaofang; Tian, Yuan; Jia, Mei; Lu, Xiang; Yue, Liang; Zhao, Xia; Jin, Weigen; Wang, Yun; Zhang, Yubao; Xie, Zhongkui; Wang, Ruoyu (Frontiers in Microbiology, 2020)
Previously, we showed that Bacillus amyloliquefaciens FZB42 can confer salt tolerance in plants by root inoculation under salt stress condition, and the FZB42 volatile organic compounds (VOCs) promoted plant growth and development under non-salt stress condition. In the present study, we investigated the mechanism that allows FZB42 VOCs to confer salt tolerance in Arabidopsis without colonization of plant roots. We found that FZB42 VOCs significantly increased the biomass of Arabidopsis and also maintained the leaf chlorophyll content under salt stress condition. Physiological tests showed that the plant anti-oxidation system was activated by FZB42 VOCs, where higher peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD) activities were detected in plants exposed to FZB42 VOCs compared with non-exposed plants. In addition, FZB42 VOCs increased the leaf total soluble sugars (TSS) content but decreased the proline content compared with the non-exposed plants. Moreover, FZB42 VOCs significantly decreased the Na+ contents of the whole plants and induced the expression of genes (NHX1; Na+/H+ exchanger 1 and HKT1; high-affinity K+ transporter 1) that function to alleviate Na+ toxicity. Furthermore, analysis of mutants with defects in specific hormone pathways showed that FZB42 VOCs induced salt tolerance in plants by modulating jasmonic acid (JA) signaling, which was confirmed by the upregulation of JA synthesis, defense-related genes, and JA biosynthesis inhibitor tests. The results of this study provide new insights into the molecular mechanism related to the interactions between plant growth-promoting rhizobacteria and plants under salt stress condition.